Pengaruh Event Cosplay Terhadap Citra Komunitas Becosplay Anime Pada Pengunjung Di Bencoolen Indah Mall Bengkulu - Parhan Juannata Kipli; Sapta Sari; Vethy Octaviani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study analyzes the influence of cosplay events on the image of the Becosplay Anime Community among visitors of Bencoolen Indah Mall, Bengkulu. Cosplay is not only viewed as a hobby but also as a form of creativity, self-expression, and a medium for promoting Japanese popular culture. This research uses a quantitative method with a survey distributed to 96 respondents selected through accidental and purposive sampling. Data were collected through questionnaires and documentation. The analysis employed validity and reliability tests, simple linear regression, t-tests, and the coefficient of determination (R²) using SPSS 26. The results show a significance value of 0.000 < 0.05, indicating a significant influence of cosplay events on community image. The Stimulus dimension in the event variable scored the highest, while the Response dimension scored the lowest. In the community image variable, Credibility emerged as the most dominant dimension, while Emotional scored the lowest. These findings suggest that visitors' perceptions are strongly shaped by event stimuli and community credibility, though improvements are needed in participant response and emotional engagement with the community.